Some issues concerning the offenses under Art. 143 of the Criminal Code - Гринчак, С. В. (Problems of legality, 2013)
The description forms of actions under Art. 143 of the Criminal Code, so as to warrant modeling four independent offenses, were investigated in the article. Substantiates the existence of the general and special rules in art. 143 of the Criminal Code.